Revolver - Kindt, Matt (DC Comics, 2021)
"REVOLVER is a tale of two worlds, and how the both test a man to his limits... Almost thirty and living in Seattle, Sam shuffles to his bed after a night out at the bars. The next morning he wakes up and catches the bus into the city, starting another day of his dead end life. But today on the radio he hears that the stock market has crashed, news of a bird-flu epidemic erupting in Asia pushes past a report of 'radioactive-material-gone-missing-in-Russia'. Did Sam really wake up this morning? The world has gone crazy--turned on its head. Sam thinks about riding the bus full loop, going home and pretending that the day hadn't started. This terrible day is capped with the destruction of Seattle... But when Sam wakes up in his small studio apartment the next morning he's confused. On the bus ride to work he listens to the radio. The world is fine... Realities begin to bleed into one another as Sam jumps between his dull-drum, everyday life and a dark apocalyptic society... but which is the real one and which one will he have to live with forever? And the most important question: does he have a choice?"--